From minority writer to Turkish exemplar: How Elif Shafak was consecrated for the Arab reader - Öztürk, Sare Rabia. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
This thesis discusses the various socio-cultural developments that gave rise to the wide recognition of Elif Shafak in the Arab field of cultural production after her novel The Forty Rules of Love was published in 2012 in Arabic translation. It overviews the changing Turkish-Arab relations, mainly in the realm of culture and ideology, from their mutual Ottoman past to their post-Ottoman present. It also revisits the changing status of Sufi mysticism (major theme of The Forty Rules of Love) in Turkish and Arabic cultures according to prevailing ideologies and popular practices of religion. It includes in the discussion each culture’s relation to the Western world, especially as regards cultural translation. It also discusses the roles played by different kinds of agency in establishing Shafak’s name in the Arab context and the dynamics of representation and cultural translation that were at play in such undertaking. Its theoretical framework is structured through reference to Pierre Bourdieu’s field theory, Homi K. Bhabha’s concepts of hybridity and cultural translation, and Mona Baker’s account of social narrative theory, combined with Nedret Kuran-Burçoglu’s synthesis of imagology and translation studies. The thesis is concluded with a descriptive and critical analysis of two samples extracted respectively from Shafak’s novels The Bastard of Istanbul and The Forty Rules of Love, the former for understanding translational actions around the Turkish identity and the latter for understanding translational actions around Sufi mysticism. The analysis incorporates the English original, the Turkish translation and the two Arabic translations of each novel.
Keywords: Reader-response criticism -- Arab countries.